Transmission of HIV infection by severe bites. (August 2019) - Thomas, Mark G; Hopkins, Christopher J; Luey, Christopher E
A 56-year-old man acquired HIV infection as the result of bites that caused severe tissue injuries. The features of the biting episode that led to transmission of infection were very similar to those in four other patients reported to have acquired HIV infection as the result of bites. Post-exposure prophylaxis should be recommended for people who have suffered bites that caused significant tissue injuries, inflicted by a person with known HIV infection, who had visible blood staining of their saliva at the time of biting, and an HIV viral load known or presumed to be greater than 3.0 log10 copies/ml.